BREEDING FOR ANTIOXIDANT CONTENT IN GRAIN AS A PROMISING TREND IN OBTAINING HEALTHY FOOD PRODUCTS - V. I. Polonskiy; I. G. Loskutov; A. V. Sumina (Вавиловский журнал генетики и селекции)
According to the Food Security Doctrine of the Russian Federation, there are plans for the nearest future to expand the assortment of healthy food products for the country’s population, so a search for relevant food sources is needed. The substances that may aid to prevent a number of serious human diseases include antioxidants, while one of the important quality parameters in food products and their ingredients is their antioxidant activity. Today, the aggregate content of antioxidants and their antioxidant activity have been identified with sufficient accuracy for vegetables and fruits. At the same time, the whole cereal grain has been found to provide higher quantities of bound polyphenols than the equivalent portion of soft fruits or widely consumed vegetables. These compounds are available for metabolism in the large intestine, and thus can produce a beneficial effect on human health. Additionally, a case study of 30 different breakfast cereals has shown that the levels of polyphenols in an average portion of oat-based cereals (40 g) are matchable with those of vegetables or fruits. It is widely known that oat and barley grains have high nutritional value, contain unsaturated fatty acids, basic minerals, proteins and β-glucans (the highest levels among cereal crops), and are characterized by the presence of diverse chemicals with antioxidant properties. In recent years, research efforts have been started in a number of Western countries to analyze the content of antioxidants in the grain of various cereal crops. In today’s Russia, only a small number of works are dedicated to studying these important chemical compounds in oat and barley grain. It should be mentioned that, although cereal crops are recognized as one of the main components in human diet, the research conducted to determine their antioxidant activity has clearly been insufficient. In order to attract the attention of Russian plant scientists, plant breeders, plant physiologists, geneticists and biotechnologists, a survey of modern publications on this problem is presented.